(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Saturated or unsaturated fatty acids compounds were administered to second-parity twins-diagnosed alpine dairy goats. Experimental groups were fed either calcium stearate (ST, n.7), fish oil (FO, n.8) or a control diet without any fat supplement (C, n.8) from one wk before (30g/head/d of fatty acids) to three wks after kidding (50g/head/d of fatty acids). ST provided 26% C16:0 and 69.4% C18:0 while FO provided 10.4% EPA and 7.8% DHA. Both ST and FO diets were formulated to be isocaloric and isonitrogenous, with the same calcium content. Previous obtained results on metabolic, productive parameters and mRNA expression of genes related to lipid metabolism and inflammatory response let us to consolidate the hypothesis that in goat lipogenesis is reduced across the transition period, if compared to cow, moreover FO can postpone or reduce lipomobilization. Based on these previous results, miRNA expression was performed on the same hepatic and adipose biopsies (collected on day -7 and 7 and 21 from kidding), as a new perspective in controlling cellular pathways, implicated in adipogenesis and metabolic and endocrine functions. We examined miR-26b and 155 for the infiltration of immune cells, miR-99a, 145 and 221 for the inflammation and lipolysis, miR-143 and 378 for pro-adipogenic function. MIXED and GLM procedures of SAS software were used for statistical analysis. No diet effect, but a time effect for miR-155 and a tendency for miR-221 were found. The increase of their expression over the time after kidding let us to speculate that goats have to face a postponed and more contained inflammation due to the lipolysis, when compared to cows.